2021
DOI: 10.1149/1945-7111/ac0551
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurement of Molecular Diffusion and Evaporation Rate of Battery Organic Electrolytes in Ambient Air

Abstract: In this paper, we measured the molecular diffusivity and evaporation rate of organic solvents—1,2-dimethoxyethane (DME), dimethyl carbonate (DMC), diethyl carbonate (DEC), and propylene carbonate (PC)—in ambient air, which are commonly used in light metal batteries, such as Li-ion, Li-air, and Na-O2 batteries. The measurement was conducted through the evolution of the evaporation rate of a liquid solvent in a glass tube, which was designed based on a one-dimensional (1-D) mass transfer model. The experiment su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The internal components of the cell are exposed for approximately 2 h in the glovebox during the insertion process, and for a small amount of time afterward while the cells are being resealed. Previous research has shown that common Li-ion battery electrolytes evaporate slowly when exposed to dry ambient air 17 , which would result in only a small decrease in conductivity consistent with the small loss of capacity seen in the modified cells.…”
Section: Resultssupporting
confidence: 54%
“…The internal components of the cell are exposed for approximately 2 h in the glovebox during the insertion process, and for a small amount of time afterward while the cells are being resealed. Previous research has shown that common Li-ion battery electrolytes evaporate slowly when exposed to dry ambient air 17 , which would result in only a small decrease in conductivity consistent with the small loss of capacity seen in the modified cells.…”
Section: Resultssupporting
confidence: 54%
“…Loss of the electrolyte due to evaporation and diffusion may also partially contribute to the observed difference. 48 In addition, the experimental reaction rate was obtained by averaging the reaction rate within each sublayer over the entire discharge period, while the model prediction considers a steady-state condition and hence a constant ORR profile. Note that the local reaction rate changed with time due to precipitate's impact, which is small due to the small volume fraction of precipitate as disclosed in the SEM images.…”
Section: Resultsmentioning
confidence: 99%